PERANCANGAN DAN PEMBUATAN ALAT UJI KOMPRESOR REFRIGERASI - Adriansyah, Willy (Mesin, 2005)
A compressor testing device based on vapor compression cycle has been designed and built successfully. Simple and easy operation is the main differences between the device and conventional compressor testing device. A reciprocating compressor performance was tested for two kind of refrigerants; R22 and HCR22 using this device. From the experimental results it is found that the isentropic efficiency can be represented by a two degrees polynomial function. The experimental results also shows that the isentropic efficiency of the compressor using R22 is higher compared to the same compressor using HCR22.